Families’ experiences of receiving adult- and pediatric-onset genetic results - Jessica Goehringer; Tracey Leitzel; Muki Kunnmann; Alyson E. Floyd; Sean O’Dell; Jessica Mozersky; Alanna Kulchak Rahm; Adam H. Buchanan (HGG Advances)
Summary: There is a scarcity of empirical data on the potential psychosocial and behavioral effects of returning genomic results for adult-onset conditions not medically actionable in pediatric patients. Potential harms include distress, discrimination, loss of future autonomy, or family functioning changes. The Pediatric Reporting of Genomic Results Study (PRoGRESS) explores outcomes of disclosing pediatric- and adult-onset genomic findings to families in an observational trial. Participants include adolescents (ages 11–17) with a genetic variant identified and returned through Geisinger’s MyCode Genomic Screening and Counseling Program and their parents. This program involves returning pathogenic and likely pathogenic variants in a list of genes consistent with the American College of Medical Genetics and Genomics secondary findings list. Parents and adolescents with pediatric- and adult-onset results were invited to participate in interviews at 1 and 12 months post results disclosure. Here, we report the results of a qualitative analysis that included data from 25 participants with a known family history of a variant. Families generally had positive or neutral experiences with learning and adjusting to the results, and, on balance, felt it was beneficial to have the result. Previously proposed hypothetical concerns regarding disclosing adult-onset results to children were not reported in this cohort. Our findings provide guidance on supporting families in preparing for and adjusting to genomic results related to adult-onset conditions, particularly in care-delivery systems that are not designed to support families as the information becomes clinically relevant and provide evidence that longitudinal support may benefit families with an adult- or pediatric-onset result.